Impatiens malipoensis S. H. Huang, a new record for the flora of Vietnam - Le, Chi Toan; Nguyen, Khang Sinh; Averyanov, Leonid V. (Hue University Journal of Science: Natural Science, 2024)
Impatiens malipoensis S. H. Huang, a narrowly distributed species previously recorded only from Southern China, is newly found in the limestone mountains of Northeast Vietnam. Its morphological description, colour illustration, ecological and phenological characteristics, and taxonomic notes are provided in this paper.